Anabolic treatments in bovines: quantification of plasma protein markers of dexamethasone administration. Issue 16 (30th June 2021) - Stella, Roberto; Bovo, Davide; Mastrorilli, Eleonora; Pezzolato, Marzia; Bozzetta, Elena; Biancotto, Giancarlo
Abstract: The aim of this study was to profile plasma proteome responses in bulls experimentally treated with dexamethasone at anabolic dosage. Illicit use of active substances in animal husbandry remains a matter of concern in Europe. Corticosteroids are probably one of the most widespread growth promoter family illegally used in beef cattle and veal calves. Testing for corticosteroids relies on detection of drug residues or their metabolites in biological fluids or tissues. Their indirect detection by mapping altered physiological parameters may overcome limits linked to route of administration, dosage, biotransformation and elimination kinetics that can lower residual drug concentration, hampering official controls. A set of 11 proteins proposed in literature as potential markers of anabolic treatments with dexamethasone, was quantified in bovine plasma by targeted proteomics based on liquid chromatography‐high resolution tandem mass spectrometry. Among investigated proteins, sex hormone‐binding globulin (SHBG), histidine‐rich glycoprotein (HRG) and paraoxonase‐1 (PON1) were found to be biomarkers of treatment. To investigate further such biomarkers, an additional group of veal calves was experimentally treated with dexamethasone at anabolic. These animals also demonstrated a significant alteration in SHBG, HRG and PON1 concentration, suggesting that quantification of plasma markers have the potential to detect animals illegally exposed to dexamethasone.